Child of an ancient city - Williams, Tad (Atheneum ; Maxwell Macmillan Canada ; Maxwell Macmillan International, 1992)
To entertain his dinner guests, Masrur, a Muslim soldier, weaves a story about his encounter with a vampire on an ill-fated caravan through the Caucassian Mountains years before.